Opportunities and limitations of BPM initiatives in public administrations across levels and institutions. - Ahrend, Norbert (My University, 2014)
In der Privatwirtschaft ist Geschäftsprozessmanagement (GPM) mittlerweile verbreitete und gängige Praxis. Um auch das Wissen zum GPM in der Verwaltung aufzubauen, den Austausch zu fördern, Geschäftsprozesse und Expertise sichtbar und für andere Verwaltungsorganisationen wiederverwendbar zu machen, wurde im Forschungsprojekt Nationale Prozessbibliothek (NPB) eine Prozess- und Kollaborationsplattform zum GPM für die deutsche Verwaltung entwickelt. Im Rahmen der Forschungsarbeit wurden wesentliche Design-Elemente dieser Plattform entworfen und einer ersten Evaluation unterworfen. Die Erkenntnisse aus der erfolgreichen Umsetzung von Prozessmanagement in der Privatwirtschaft sind nicht ohne weiteres in die Verwaltungspraxis übertragbar. Die Arbeit unternimmt in einem Beitrag einem Vergleich für Geschäftsprozessmanagement in der öffentlichen Verwaltung in den Ländern Deutschland, Schweiz und Österreich. In einem weiteren Beitrag, wird untersucht, welche Umstände, Treiber und Hemmnissen den Prozesswissens-Austausch in öffentlichen Organisationen beeinflussen. In einem abschließenden Beitrag werden dann die wesentlichen Bausteine eines föderalen Informationsmanagements in der öffentlichen Verwaltung in Deutschland dargestellt. Dabei wird untersucht, wie Daten und Informationen aus den Bereichen Leistungen, Prozesse und Formulare der öffentlichen Verwaltung miteinander zu kombinieren und zu integrieren sind.

The goal of the research project "National Process Library"1 (NPL) is to create a platform to exchange and reuse processes and BPM expertise about and among German administrations. For the dissertation at hand, essential design elements of this platform have been designed and have been subject to a first evaluation (chapter 3). Many findings about the successful implementation of process management in the private sector cannot be directly transferred to the public administration, as there exist important differences. First, traditional process reengineering approaches cannot be applied in public administrations due to legal and political conditions. Second, the wide range of services, which are typically offered by public administrations represent a particular challenge in this context. Hence, the second contribution (chapter 4) focuses on the different implementation strategies of BPM in public administrations in Europe. We compared the approaches to business process management in the public administration of three countries, namely Germany, Switzerland, and Austria. The goal of this contribution is to identify successful implementation strategies. The third contribution (chapter 5) investigates the circumstances, drives and inhibitors to improve process knowledge sharing in public organizations. The last contribution (chapter 6) represents the essential components of a federal information management in the public administration in Germany. The derived framework combines and integrates data and information from the areas of services, processes and forms of public administrations. To this end, we identify the essential relationships and effects of these areas on the administrative action.
Keywords: Verwaltung; Verwaltungsorganisation; Information; Management; Verwaltungswissenschaft; Kooperation; Geschäftsprozess; E-Government; Wissensmanagement; Informationsmanagement